The Transition Toward Nitrogen Deprivation in Diatoms Requires Chloroplast Stand-By and Deep Metabolic Reshuffling - Scarsini, Matteo; Thiriet-Rupert, Stanislas; Veidl, Brigitte; Mondeguer, Florence; Hu, Hanhua; Marchand, Justine; Schoefs, Benoît (Frontiers in Plant Science, 2022)
Microalgae have adapted to face abiotic stresses by accumulating energy storage molecules such as lipids, which are also of interest for industries. Alas, the impairment in cell division during the accumulation of these molecules constitutes a major bottleneck for the development of efficient microalgae-based biotechnology processes. To address the bottleneck a multidisciplinary approach was used to study the mechanisms involved in the transition from nitrogen-replete to nitrogen starvation conditions in the marine diatom Phaeodactylum tricornutum cultured in a turbidostat. Combining data demonstrate that the different steps of nitrogen deficiency clustered together in a single state in which the cells are in equilibrium with their environment. The switch between the nitrogen-replete equilibrium and the nitrogen-deficiency equilibrium is driven by the intracellular nitrogen availability. The switch induces a major gene expression change, which is reflected in the reorientation of the carbon metabolism toward an energy storage mode while still operating as a metabolic flywheel. Although the photosynthetic activity reduced, the chloroplast is kept in a stand-by mode allowing a fast resuming upon nitrogen repletion. Altogether, these results contribute to the understanding of the intricate response of diatoms under stress.